GAMBARAN ASUPAN ZAT GIZI MAKRO, ANTIOKSIDAN SERTA POLA MAKAN PADA PASIEN KANKER PAYUDARA STADIUM III DENGAN KEMOTERAPI DI RSI SITI KHADIJAH PALEMBANG: breast cancer - Azzahara, Alda Oktaria; siregar, afriyana; sriwiyanti (JURNAL SVASTA HARENA RAFFLESIA, 2024)
Breast cancer (ca mammae) originates from the uncontrolled growth and division of cells in the breast tissue, forming lumps. This study aims to analyze the intake of macronutrients (energy, protein, fat, carbohydrates), antioxidants (vitamins A, C, E, and zinc), and eating patterns in stage III breast cancer patients undergoing chemotherapy at RSI Siti Khadijah Palembang. The research method used is descriptive with a cross-sectional design. The study population consists of all cancer patients receiving chemotherapy in the chemotherapy room at RSI Siti Khadijah Palembang, selected using proportion sampling. The sample size is 36 individuals. This study was conducted from April to May 2024. Data were collected through direct interviews using questionnaires, food recall forms, and food frequency questionnaires. The results revealed that among the 36 respondents, 51.4% had energy intake below requirements, 67.6% had adequate protein intake, 70.3% had adequate fat intake, 54.1% had adequate carbohydrate intake, 67.9% had insufficient vitamin A intake, 51.4% had adequate vitamin C intake, 61.6% had insufficient vitamin E intake, and 64.9% had adequate zinc intake. Breast cancer patients undergoing chemotherapy at RSI Siti Khadijah experienced decreased appetite, nausea, and vomiting, leading to nutritional imbalances. The study also found that the FFQ tended to overestimate certain types of foods contributing to macronutrient and vitamin intake.